Rabbit for meat and wool production in India: A review - Risam, K S; Das, G K; Bhasin, V (The Indian Journal of Animal Sciences, 2005)
Rabbit husbandry has vast potential to improve the socio-economic status of the rural poor and to provide fond security in terms of low cost animal protein. The total rabbit populalion of the country is about 406 000. Out uf the 28 states and 7 UTs surveyed, 27 states and 5 UTs, have rabbit population. Rabbit is highly prolific. A female rabbit, through its progenies can produce up to 80 kg of meat per year i.e. 2900 to 3 000% of her live weight. Meat production in lndia is reported to be between 5 000 and 19000 tonnes/year. Angora wool production is 25 to 30 tonnes per year, which is 1% o f estimated global production. In rabbit breeding, several production and reproduction traits were studied in relalion to genetic improvement programme through selection of individual. The estimates of different genetic parameters in retation to production and reproduction traits have been discussed. Heritability estimates for different parameters, meat production meat quality and pelt quality were also studied. Reports on mortality pattern have also been analyzed.Areas for future rabbit research in India have also been discussed in view of present research status and future needs.